2021
DOI: 10.1111/tpj.15617
|View full text |Cite
|
Sign up to set email alerts
|

Jujube metabolome selection determined the edible properties acquired during domestication

Abstract: Plants supply both food and medicinal compounds, which are ascribed to diverse metabolites produced by plants. However, studies on domestication-driven changes in the metabolome and genetic basis of bioactive molecules in perennial fruit trees are generally lacking. Here, we conducted multidimensional analyses revealing a singular domestication event involving the genomic and metabolomic selection of jujube trees (Ziziphus jujuba Mill.). The genomic selection for domesticated genes was highly enriched in metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…Selection of malic acid and triterpene metabolites during domestication leads to edible properties of Jujube ( Zhang et al, 2021 ), suggesting that genomic selection caused by domestication and/or environment can lead to markedly different varieties. Hemp originated in Central Asia and gradually spread around the world and domesticated into varieties with different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of malic acid and triterpene metabolites during domestication leads to edible properties of Jujube ( Zhang et al, 2021 ), suggesting that genomic selection caused by domestication and/or environment can lead to markedly different varieties. Hemp originated in Central Asia and gradually spread around the world and domesticated into varieties with different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The data generated represents an advance to the genetic/biochemical resources available in cassava. For example, the present study has facilitated the further identification of metabolites by clustering of genotypes, and enables future association studies using GWAS approaches (28)(29)(30). Similar approach has been applied in tomato and maize (31,32).…”
Section: Discussionmentioning
confidence: 82%
“…In addition to co‐occurrence, precursor peptides appear to be transcriptionally co‐regulated with a split BURP. Published work from Z. jujuba showed that sanjoinine A content was most closely associated with transcript levels of a genomic locus containing both a split BURP and methyltransferase [21] . We also analyzed the ATTED‐II database [22] for genes co‐expressed with putative precursor peptides from Arabidopsis thaliana , Vitis vinifera, Populus trichocarpa, Glycine max, Medicago truncatula , and Solanum lycopersicum .…”
Section: Figurementioning
confidence: 99%